The Changes of the Basic Rights in the Current Constitution of China - W. Weiming; N. Symaniuk (BRICS Law Journal, 2024)
The current Constitution of the People’s Republic of China is the 1982 Constitution, which is the fourth constitution after the founding of the People’s Republic of China. The provisions of the current Constitution on the fundamental rights of citizens are generally similar to those of the first Constitution of 1954, but are more specific, while the freedom of movement provided for in the 1954 Constitution is deleted. The 1975 Constitution and the 1978 Constitution are the second and third Constitutions, respectively. Because of their special historical period, the provisions on fundamental rights in these two constitutions are retrogressive and failing. The historical background of the revision of the Constitution, the possibility of realizing rights and the level of social development are the main reasons for determining the provisions of the basic rights of citizens in the 1982 Constitution. In 2004, the current Constitution was amended to include “the State respects and protects human rights,” which establishes the constitutional obligation of the State to guarantee human rights. In practice, there is still ongoing debate over how the State’s guarantee obligations are implemented and whether citizens can file lawsuits if they believe that their fundamental rights have been violated. In recent years, the recordation review has partially realized the supervision of legislation that may infringe on citizens’ basic rights by reviewing the constitutionality and legality of laws and regulations, but citizens have not been able to directly protect their rights through litigation. The changes in the basic rights of citizens in terms of constitutional provisions and legal guarantees over the past 40 years are the result of the development of the rule of law in China. In order to more effectively solve the problem of constitutional rights from text to reality, it is also necessary to further develop the constitutional review system.